Downregulation of microRNA-181d had suppressive effect on pancreatic cancer development through inverse regulation of KNAIN2 - Guopeng Zhang; Dongbo Liu; Guoxian Long; Lei Shi; Hong Qiu; Guangyuan Hu; Guoqing Hu; Shunfang Liu (Tumor Biology)
We explored the expression and function of miR-181d (microRNA-181d) in human pancreatic cancer. Quantitative real-time polymerase chain reaction was used to probe miR-181d expression in both pancreatic cancer cell lines and human pancreatic carcinoma. Pancreatic cancer cell lines, PANC-1 and AsPC-1 cells, were engineered to stably downregulate endogenous miR-181d through lentiviral transduction. The mechanistic effects of miR-181d downregulation on pancreatic cancer development were tested by proliferation, migration, fluorouracil chemosensitivity assays in vitro, and explant assay in vivo. Possible miR-181d downstream gene, NKAIN2 (Na+/K+ transporting ATPase interacting 2), was tested by dual-luciferase activity assay and quantitative real-time polymerase chain reaction. Functional involvement of NKAIN2 in miR-181d-regulated pancreatic cancer development was tested by small interfering RNA–mediated NKAIN2 knockdown in miR-181d-downregulated PANC-1 and AsPC-1 cells. MiR-181d was upregulated in both pancreatic cancer cell lines and human pancreatic carcinoma. Lentivirus-induced miR-181d downregulation decreased pancreatic cancer proliferation, migration, and fluorouracil resistance in vitro and inhibited the growth of cancer explant in vivo. NKAIN2 was directly targeted by miR-181d in pancreatic cancer. Small interfering RNA–mediated NKAIN2 knockdown reversed the inhibition of miR-181d downregulation on pancreatic cancer development. MiR-181d is aberrantly overexpressed in pancreatic cancer. Inhibiting miR-181d may suppress pancreatic cancer development, possibly through the inverse regulation on NKAIN2.